The role of adipose-derived stem cells-derived extracellular vesicles in the treatment of diabetic foot ulcer: Trends and prospects - Deng, Hongyan; Chen, Yong (Frontiers in Endocrinology, 2022)
Diabetic foot ulcer(DFU) is one of the most severe chronic complications of type 2 diabetes mellitus, which is mainly caused by peripheral vascular occlusion with various degrees of infection. Treatment of DFU is difficult, and ulcer formation in lower limbs and deep-tissue necrosis might lead to disability or even death. Insulin resistance is the major mechanism of type 2 diabetes mellitus development, largely caused by adipose tissue dysfunction. However, adipose tissue was recently identified as an important endocrine organ that secretes bio-active factors, such as adipokines and extracellular vesicles(EVs). And adipose tissue-derived stem cells(ADSCs) are abundant in adipose tissue and have become a hot topic in the tissue engineering field. In particular, EVs derived from ADSCs contain abundant biomarkers and mediators. These EVs exert significant effects on distant cells and organs, contributing to metabolic homeostasis. In this review, we aim to elaborate on the mechanisms of diabetic non-healing wound development and the role of ADSCs-EVs in wound repair, which might provide a new therapy for treating DFU.